Application Of The Viola Jones Algorithm On Face Detection - Joyanda Hasiholan Sinurat (CV. AFDIFAL MAJU BERKAH, 2024)
The face is the central organ for human expression, recognition, and communication. The face consists of four very important sense organs, namely the nose, eyes, ears, and tongue. The human brain has the privilege of recognizing someone based on their face. Face Detection is used to find out faces or nonfaces in an image and this section is the first step in the face detection process so its presence is very vital. Face detection task is very easy for humans, but this task is very complicated for computers because there are several stages that must be passed to detect faces. Where in this study the author designed and made an application for the application of the viola jones algorithm on face detection by discussing Python programming and using the Mysql database. The application of the viola jones algorithm on face detection goes well. Faces can be recognized by the application and display face owner information. Where the test is divided into 5 (five) including lighting testing with a test percentage level of 66.67% of detected faces, testing distance testing of 100% of faces detected at a distance of 1-100 cm, testing the number of faces there are 6 (six) results detected with 2 (two) faces, where faces must be approximately 10 cm apart so that faces can be detected and no results are detected on 3 (three) faces. So it can be concluded that the application cannot capture all faces detected by the camera. different face testing percentage test 100% the application can detect different people's faces with a single face.